Tempo interpretation of Debussy’s Images Book 2 - Wong, Suet Li (2020)
Many amateurs or professional performers usually encounter a major challenge in determining an appropriate tempo of the twentieth-century music. Despite the tempo marking is usually uniform, most pianists have different interpretation results from the sources often mention the desirability of non-literal implementation. The objective of the study was to investigate the ambiguity of tempo in Debussy’s Images Book 2 in the hope to obtain a more faithful interpretation in performance. This study made use of qualitative methods research design.